Osteon orientation of the diaphysis of the long bones in man - Hert, J; Fiala, P; Petrtýl, M (Bone, 1994)
The orientation of osteons has been described in the long bones of man, using a special macroscopic method, which enabled the study of the osteonal architecture throughout the extent of the diaphysis. The osteons in all bones are arranged in two helical systems of opposite directions, which lie on the opposite sides of the diaphysis. The inclination of osteon direction from the bone axis in remarkably constant, varying between 5 degrees and 15 degrees. The boundary between the two fields is sharp. This special type of osteon orientation corresponds with the directions of the maximum principal stress and/or strain in the walls of the bones, which are exposed to both the bending and torque moments. The typical orientation of osteons reflects the history of loading of the bones in the course of physiological activity. The dominant stress state of every bone could be deduced from the osteon orientation and from the position of the pressure and tension fields on the surface of the bone.
Keywords: tibie; Humerus; biomechanika; humerus; Biomechanical Phenomena; Bone and Bones; Femur; kosti a kostní tkáň; Radius; radius; femur; dospělí; Humans; Tensile Strength; Adult; Tibia; lidé; pevnost v tahu